2008
DOI: 10.2337/dc08-0075
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Insulin on Glycemic Control and β-Cell Function in Newly Diagnosed Type 2 Diabetes With Severe Hyperglycemia After Short-Term Intensive Insulin Therapy

Abstract: OBJECTIVE -To evaluate whether treatment with insulin is advantageous compared with oral antidiabetes agents in newly diagnosed type 2 diabetes with severe hyperglycemia after short-term intensive insulin therapy.RESEARCH DESIGN AND METHODS -Newly diagnosed type 2 diabetic patients with severe hyperglycemia were hospitalized and treated with intensive insulin injections for 10 -14 days. The oral glucose tolerance test (OGTT) was performed after intensive insulin treatment. After discharge, the patients were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
139
5
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 23 publications
5
139
5
5
Order By: Relevance
“…Intensive insulin therapy, such as multiple insulin injections or continuous subcutaneous insulin infusion, has been reported to be effective for near-normoglycemic remission in newly diagnosed T2DM patients [5,6]. However, the frequency of daily insulin injections had no significant association with the cessation of insulin therapy in the present study.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…Intensive insulin therapy, such as multiple insulin injections or continuous subcutaneous insulin infusion, has been reported to be effective for near-normoglycemic remission in newly diagnosed T2DM patients [5,6]. However, the frequency of daily insulin injections had no significant association with the cessation of insulin therapy in the present study.…”
Section: Discussioncontrasting
confidence: 53%
“…However, we did not have data of CPR in all subjects and it has not been elucidated whether these markers become predictors of the cessation of insulin therapy. Conversely, it has been reported that β-cell function in newly diagnosed T2DM patients recovers following intensive insulin therapy [5,6]. These observations suggest that remission may occur more commonly in patients with a shorter duration of diabetes because β-cell function in these patients has the potential to recover.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…3,118 The effect of short-term IIT early in T2D was to improve betacell function (first-phase insulin response, HOMA-B and proinsulin:insulin ratio). 3,117,119 Restoration of first-phase insulin secretion predicted maintenance of euglycaemia at one year. 3 What were the characteristics of the responders to IIT?…”
Section: Early Intensive Insulin Therapy (Iit)mentioning
confidence: 99%